Android app for automatic music composition - Nieto, Marina S.; Barbancho-Pérez, Ana María; Barbancho-Pérez, Isabel; Tardón-García, Lorenzo José (My University, 2018)
In this contribution, we present an Android App that generates music automatically replicating a specific contemporary genre, specifically rock music. The composition system is based on the analysis of a set of songs of the desired genre. The analysis results the automatic composition algorithm requires are exported to a JSON file that can be readily imported and parsed. The Android App developed creates a symbolic representation of the music generated for drums, bass and rhythm guitar that can be exported to a MIDI file or audio waveform. The evaluation results show that the automatic compositions generated are not distinguished amongst other excerpts created by human composers.
Keywords: Aplicaciones para móviles; Composición musical; Music information retrieval; Automatic composition; App; Android